Autoavaliação de um centro universitário da Paraíba no contexto do Sistema Nacional de Avaliação da Educação Superior: análise das contribuições dos relatórios institucionais (2017-2020) - Viana, Suely Aragão Azevêdo (2021)
This thesis is linked to the Educational Policies Line of Research within the thematic Higher Education Evaluation axis of the Education Graduate Program belonging to the Federal University of Paraíba (PPGE-UFPB). This study is inserted in the higher education institutional assessment field in Brazil, established after the publication of Law No. 10,861 of April 14, 2004. The National Higher Education Assessment System (Sistema Nacional de Avaliação da Educação Superior - SINAES) aims to ensure improvements concerning higher education quality, guiding its supply increase, expanding the permanence of institutional effectiveness and promoting the deepening of the institutions' social commitments and responsibilities based on respect for differences and diversity, as well as autonomy and institutional identity affirmation. Thus, the general objective comprised the analysis of the results presented in IES Self-Assessment Reports under the perspective of SINAES guidelines to support the institutional management of the University Center – UNIESP. The present investigation is an applied research comprising a qualitative approach, and, concerning the objectives, consists in an exploratory research. Considering the adopted procedures, bibliographic, documentary and case study research were employed, and the collected data were analyzed applying the SWOT Analysis, used as a tool to identify the strengths, weaknesses, opportunities, and threats that positively or negatively affect the quality of education within an UNIESP scope, and the sample consists of four Internal Institutional Assessment Reports (Relatórios de Avaliação Institucional Interna - RAAI's). This study demonstrated that the UNIESP's Self Evaluation Committee (Comissão Própria de Avaliação - CPA) has been carrying out IES self-assessments in accordance to current Brazilian legislation, as 42 of the fifty indicators drawn up by SINAES established in 2017 were already included, while 37 were addressed in 2018. In 2019, only five of the indicators were covered, while in 2020, 40 indicators were covered, with the predominance of indicators fully covered in the analyzed RAAI's. This study also showed that UNIESP annually develops its self-assessment process effectively so that it takes ownership of the results in order to support the decision-making of managers. However, it is necessary that the CPA intensify awareness among students, teachers and staff so that a greater number of people can participate in the AAI, since we found from the analysis of the RAAI issued in 2018, that only 2,736 students responded to the questioning regarding the quality of education offered in 2017, a total that we believe to be much lower than the total number of students enrolled in undergraduate courses, given the size of the institution. The findings demonstrate that the institution has present significant improvements in teaching-learning and administrative processes, which can also be attributed to the effective role of the CPA, which allows managers to identify the institution's weaknesses and plan alternatives to overcome encountered obstacles.